Bioactivity-Guided Evaluation of Tabernaemontana divaricata Leaf Fractions Reveals Promising Anti-Inflammatory, Antipyretic, and Analgesic Effects in Mice - Chaerul Fadly Mochtar (Universitas Airlangga, 2025)
Inflammation, pain, and fever are major physiological responses to tissue injury or infection that often require pharmacological intervention. However, prolonged use of non-steroidal anti-inflammatory drugs (NSAIDs) may cause gastrointestinal and hepatic toxicity, encouraging the search for safer natural alternatives. Tabernaemontana divaricata has been traditionally used to treat inflammatory and febrile conditions, yet limited studies have evaluated the pharmacological properties of its solvent fractions. This study aimed to assess the anti-inflammatory, antipyretic, and analgesic activities of the hexane (HeFrTD) and butanol (BuFrTD) fractions derived from the ethyl acetate extract of T. divaricata leaves in male mice. The fractions were obtained through liquid–liquid partitioning and administered orally at doses of 62.5, 125, and 250 mg/kg body weight. Anti-inflammatory, antipyretic, and analgesic effects were evaluated using carrageenan-induced paw edema, peptone-induced pyrexia, and hot plate assays, respectively. Statistical analysis was conducted using one-way ANOVA followed by Bonferroni’s post hoc test. Both fractions significantly (p < 0.05) reduced inflammation, pyrexia, and pain in a dose-dependent manner. The 250 mg/kg dose produced strong anti-inflammatory and antipyretic responses, with no statistically significant difference from diclofenac and paracetamol within the experimental model. Analgesic activity suggested possible involvement of central pathways commonly associated with opioid receptor modulation. In conclusion, the fractions of T. divaricata exhibit notable multi-target pharmacological effects, supporting their traditional use and potential for development as natural anti-inflammatory, antipyretic, and analgesic agents.